OF WHICH BODY ONE TALKS ABOUT IN NURSING QUOTIDIAN - Vanúzia Sari; Carmem Lúcia Colomé Beck; Lúcia Beatriz Ressel; Rosângela Marion da Silva; Graciela Dutra Sehnem; Juliana Petri Tavares (Universidade Federal do Paraná, 2009)
This study aimed to identify and analyze the conceptions of patient's body and care giver's body. It is aresult of a bibliographical research on the material produced in the period from 1997 to 2006. Data were collected in theLILACS and SCIELO databases, using the following keywords: nursing, body, corporeity and nursing care. The samplewas made up of 10 studies (four dissertations, one these and six articles). Data analysis was based on Thematic Analysis.The results pointed categories: body as object; mechanized body; ritualized body; sexual body; and alienated/docilebody. The importance of the development of a professional conscience is pointed out, that should focus on the conceptsof an experienced and valued body, instead of the concepts of the docile and object body. The need of discussion on thetheme for the health care and nursing professional formation is stressed, considering that the body dimension of theworkers is silent, invisible throughout the academic discussion and professional practice.